2003
DOI: 10.1029/2002ja009791
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal structure of storm‐time chorus

Abstract: [1] We discuss chorus emissions measured by the four Cluster spacecraft at close separations during a geomagnetically disturbed period on 18 April 2002. We analyze the lower band of chorus below one half of the electron cyclotron frequency, measured at a radial distance of 4.4 Earth's radii, within a 2000 km long source region located close to the equator. The characteristic wave vector directions in this region are nearly parallel to the field lines and the multipoint measurement demonstrates the dynamic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
466
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 387 publications
(504 citation statements)
references
References 39 publications
(55 reference statements)
37
466
1
Order By: Relevance
“…This type of frequency time structure is observed at Jupiter (Gurnett and Scarf, 1983) as well as the Earth (e.g., Burtis and Helliwell, 1969;Tsurutani and Smith, 1974;Santolík et al, 2003) and Saturn . Individual chorus bursts may only last a few milliseconds, but they often overlap in time and occur repeatedly for periods of hours and longer.…”
Section: Calculating Diffusion Coefficientsmentioning
confidence: 98%
“…This type of frequency time structure is observed at Jupiter (Gurnett and Scarf, 1983) as well as the Earth (e.g., Burtis and Helliwell, 1969;Tsurutani and Smith, 1974;Santolík et al, 2003) and Saturn . Individual chorus bursts may only last a few milliseconds, but they often overlap in time and occur repeatedly for periods of hours and longer.…”
Section: Calculating Diffusion Coefficientsmentioning
confidence: 98%
“…The subsecond time scale is many orders of magnitude quicker than time scales for quasi-linear diffusion appropriate to previously known whistler populations which had amplitudes of up to ∼30 mV/m [Santolík et al, 2003] but are more typically observed with amplitudes of <1 mV/m.…”
Section: Introductionmentioning
confidence: 99%
“…Complex fine structure of chorus wave packets was recently found in their source region . The sources of chorus are located within a few thousands of km of the equatorial plane (Dunkel and Helliwell, 1969;Burtis and Helliwell, 1969;Burton and Holzer, 1974;Tsurutani and Smith, 1977;Nagano et al, 1996;LeDocq et al, 1998;Santolík et al, 2003b), with scales of the order of a few wavelengths perpendicular to the field lines (Santolík and Gurnett, 2003). Chorus thus propagates from its well localized source in the vicinity of the equatorial plane, but no evidence of reflected chorus waves returning to the equator was found until recently.…”
Section: Introductionmentioning
confidence: 99%